Nitenpyram biodegradation by a novel nitenpyram-degrading bacterium, Ochrobactrum sp. strain DF-1, and its novel degradation pathway - Wang, Guangli; Chen, Mengqing; Jiang, Li; Zhang, Yunfang (Frontiers in Microbiology, 2023)
Nitenpyram is a neonicotinoid insecticide that is commonly found in the environment. However, its biodegradation by pure cultures of bacteria has not been widely investigated and the catabolic pathway(s) for nitenpyram metabolism remain elusive.In this study, the aerobic strain DF-1, isolated from a wastewater-treatment pool contaminated with nitenpyram. The strain was designated an Ochrobactrum sp. utilizing a combination of traditional methods and molecular ones. Strain DF-1 can use nitenpyram as a sole carbon or nitrogen source for growth. In liquid medium, 100 mg• L -1 nitenpyram was metabolized to undetectable levels within 10 d. Four metabolites were found by gas chromatography-mass spectrometry (GC-MS) analyses during nitenpyram degradation. According to the aforementioned data, a partial metabolic pathway of nitenpyram was proposed of strain DF-1. Inoculation of strain DF-1 promoted nitenpyram (10 mg• kg -1 ) degradation in either sterile or non-sterile soil. To our knowledge, this is the first characterization of nitenpyram degradation by a specific bacterium and likely to be exploited for the remediation of nitenpyram-contaminated sites.